2016
DOI: 10.1038/ncomms10485
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of graded phosphorylation into switch-like nuclear translocation via autoregulatory mechanisms in ERK signalling

Abstract: The phosphorylation cascade in the extracellular signal-regulated kinase (ERK) pathway is a versatile reaction network motif that can potentially act as a switch, oscillator or memory. Nevertheless, there is accumulating evidence that the phosphorylation response is mostly linear to extracellular signals in mammalian cells. Here we find that subsequent nuclear translocation gives rise to a switch-like increase in nuclear ERK concentration in response to signal input. The switch-like response disappears in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 50 publications
8
35
0
Order By: Relevance
“…While Spry2/4 and Etv4/5 are detected in all ICM cells, Dusp4 expression correlates with PrE (Figure 6B and S6). These downstream targets can regulate the MAPK/ERK cascade via positive and negative feedback to produce specific context-dependent responses (Brewer et al, 2016; Buday et al, 1995; Ekerot et al, 2008; Kholodenko, 2006; Shindo et al, 2016; Vasudevan and Soriano, 2016). Therefore, the association of EPI- and PrE-biased cells with distinct targets indicates that differential levels of FGF signaling in lineage-biased cells may be augmented by distinct feedback (Figure 6A).…”
Section: Discussionmentioning
confidence: 99%
“…While Spry2/4 and Etv4/5 are detected in all ICM cells, Dusp4 expression correlates with PrE (Figure 6B and S6). These downstream targets can regulate the MAPK/ERK cascade via positive and negative feedback to produce specific context-dependent responses (Brewer et al, 2016; Buday et al, 1995; Ekerot et al, 2008; Kholodenko, 2006; Shindo et al, 2016; Vasudevan and Soriano, 2016). Therefore, the association of EPI- and PrE-biased cells with distinct targets indicates that differential levels of FGF signaling in lineage-biased cells may be augmented by distinct feedback (Figure 6A).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in mammalian cells have shown specific feedback mechanisms that modulate nuclear ERK activity. These mechanisms include the facilitation of nuclear import and export of ERK by EGF signals (Ando, Mizuno, & Miyawaki, ) and the conversion of graded ERK activity in response to different levels of RTK stimulus into a threshold response of nuclear ERK through facilitated nuclear translocation (Shindo et al, ). The latter study demonstrated that the facilitated nuclear translocation achieves the nuclear accumulation of ERK within 8 min of RTK stimulation at the threshold concentration of ~0.05 mg/ml EGF.…”
Section: Discussionmentioning
confidence: 99%
“…D. Weber, Raben, Phillips, & Baldassare, 1997). The graded mammalian ERK activation in response to cellular stimuli is converted to a switch-like mechanism to control c-fos induction during the immediate-early gene response (Mackeigan, Murphy, Dimitri, & Blenis, 2005), in part through regulation of ERK nuclear translocation (Shindo et al, 2016). With only transient ERK activation, c-Fos and other IEG protein products are synthesized, but are unstable and quickly become degraded (Murphy et al, 2002).…”
Section: Erk Substratesmentioning
confidence: 99%